Kulturowa recepcja biblijnego „drzewa życia” (w chrześcijańskiej tradycji i lekturze ponowoczesnej) - Kogut, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The Christian “Lifetree” seems to be often omitted today in its fundamental role as the one, which brings us Christ’s redemption. As for Christians the “Lifetree” is the cross, Jesus Christ itself, His torment and resurrection, redemption of human from the original sin, and thereby giving him the eternal life. This way-in purely general terms- could be answered the question: what signifies the term “Lifetree” for Christians. However in order to explain it rightly, we need to relay on the Holy Scripture and look at its beginning, at Genesis, which explained us the world formerly an today-unfortunately- tends to be seen as fairy tale, which should moralize the human and teach him to obey God. No wonder, that the human has lost his ability to understand the reality and like by snake deceived Eve in paradise, is confused. Jesus said: “I am the way and the truth and the life. No one comes to the Father except through me” (J 14,6). However today-in the modern world involved in sin-this Truth is being questioned increasingly in its essential value.
Keywords: “Lifetree”; Christianity; Cross; Christ; original sin; Protoevangelium; Genesis